Marshland Colonization in Acadia and Poitou during the 17th Century - Kennedy, Gregory (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2013)
This article compares marshland colonization in Acadia and France during the 17th century.  It begins with an analysis of why  the initial attempts to colonize marshlands failed.  It then compares the later, successful initiatives at Port Royal, in Acadia, and the Poitevin Marsh, in France.  Although they had very different objectives and tackled very different environmental challenges, both groups effectively organized their activities and used innovation in adapting old techniques. What made Acadian marshland farming distinctive was its small scale and its dispersed, decentralized nature.   Both initiatives demonstrate how successful marshland colonization was a profoundly local endeavour.